Diseño modular de instrumentación virtual para la manipulación y el análisis de señales electrofisiológicas - Lemus-Aguilar, I.; Bargas, J.; Tecuapetia, F.; Galárraga, E.; Carrillo-Reid, L. (Revista Mexicana de Ingenieria Biomedica, 2006)
The electrophysiology interest in the electrical properties of neurons is based on discover the way in which the brain stores and transfers the information, while the engineering interest tries to use the neuron as a pattern for the creation of neural networks and computer design. There are different techniques for studying the neuronal intrinsic properties as well as the form in which neurons establish connections between them. The more common are: the intracellular recording, the field recording, and the voltage-clamp and current-clamp whole-cell recording techniques. There is a commercial tendency to develop hardware and software systems, which only use one of these techniques, increasing the cost of basic research. The present project: called DENDRON is a flexible tool that can be used with all the above techniques. It has two function generators and four input channels, even it allows the user to realize the on-line analysis of different protocols used commonly in electrophysiology. The acquired data and the analysis results are stored in the hard disk. The modular design of the software makes it easily adaptable for specific user requirements without drastic modifications nor new hardware.